2023
DOI: 10.3390/ijms24043923
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Regulation of mTOR Signaling via Ca2+-Binding Proteins

Abstract: Environmental factors are important regulators of cell growth and proliferation. Mechanistic target of rapamycin (mTOR) is a central kinase that maintains cellular homeostasis in response to a variety of extracellular and intracellular inputs. Dysregulation of mTOR signaling is associated with many diseases, including diabetes and cancer. Calcium ion (Ca2+) is important as a second messenger in various biological processes, and its intracellular concentration is tightly regulated. Although the involvement of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 139 publications
1
5
0
Order By: Relevance
“…Ca homeostasis was critical for regulating the lysosome function as one of the main storage compartments for Ca . mTORC1 played a key role in the regulation of lysosomal pH and catabolic activity, , while the activation of mTORC1 highly depended on the Ca-binding proteins. , Compared with Ca, Zn homeostasis also regulated the lysosome function. Rivera et al found that the loss of Zn transporter inhibited the assembly of the proton transporter vacuolar ATPase on lysosomes, which thereby affected the lysosome acidification.…”
Section: Resultsmentioning
confidence: 99%
“…Ca homeostasis was critical for regulating the lysosome function as one of the main storage compartments for Ca . mTORC1 played a key role in the regulation of lysosomal pH and catabolic activity, , while the activation of mTORC1 highly depended on the Ca-binding proteins. , Compared with Ca, Zn homeostasis also regulated the lysosome function. Rivera et al found that the loss of Zn transporter inhibited the assembly of the proton transporter vacuolar ATPase on lysosomes, which thereby affected the lysosome acidification.…”
Section: Resultsmentioning
confidence: 99%
“…A recent bioRxiv preprint study by Kazyken and colleagues reported that alkaline intracellular pH can activate the AMPK/mTORC2 pathway and inhibit mTORC1 activity [165]. This links the role of SGLT2is to AMPK activation and subsequent mTORC2 activity via NHE-mediated pH homeostasis and Ca i 2+ modulation [64]. From another perspective, SGLT2 inhibitors have been shown in some studies to promote ketogenesis, lipid oxidation, and erythrocytosis, which can reflect a fasting-like transcriptional paradigm by mimicking nutrient deprivation and hypoxia [166] but can also be responsible for the moderate adverse effects in SGLT2i clinical trials (Table 2).…”
Section: Moderate Genital Infectionsmentioning
confidence: 98%
“…mTOR signaling is involved in diverse biological pathways by regulating ionic homeostasis, specifically by regulating the activity and expression of various Ca 2+ channels [61][62][63]. Intertwined links between sarcoplasmic reticulum calcium homeostasis and mTORC1 signaling are critical for physiological and pathological cardiac hypertrophy [64,65]. Inhibition of mTORC1 with rapamycin induces Ca 2+ release from lysosomes through the activation of two-pore segment channel 2, TPC2 [66].…”
Section: Differential Role Of Mtorc1 and Mtorc2 In Diabetic Cardiomyo...mentioning
confidence: 99%
“…Despite varying modes of regulation, the different family members are modulated by mTORC2. Whether the signals that activate PKC could play a role in modulating mTORC2 remains a possibility given that mTORC2 components can bind to different lipids and that this complex is regulated by calcium/calmodulin [ 132 , 189 , 250 ]. The TM and HM phosphorylation of PKC occurs in an mTORC2-dependent manner as disruption or pharmacological inhibition of mTORC2 abolishes their phosphorylation.…”
Section: Targets and Cellular Functions Of Mtorc2mentioning
confidence: 99%